Analysis of the nutrient profile in organic manure from Romanian animal farms - Ioana-Mihaela Jagă; Carmen Postolache; Florina Botez; Florica Bărbuceanu; Luminita Romașcu; Luminita Marutescu; Marcela Popa; Corneliu Vrancianu (Journal of Central European Agriculture)
The livestock industry has a harmful effect on the environment and contributes to climate change by producing significant amounts of greenhouse gases such as carbon dioxide (CO2), nitrous oxide (N2O), methane (CH4), and ammonia (NH3). In line with this, the production and composting of manure is an important issue in livestock farming. During composting, the manure undergoes physical and nutritional profile changes, which can affect the environment. In this context, in the present study, we have investigated the dynamics of the chemical parameters such as pH, humidity (U%), organic matter (MO%), ammonium nitrogen N-NH4+ (g/kg), nitrogen in the form of nitrite N-NO2- (g/kg), nitrate nitrogen N–NO3- (g/kg) and phosphorus phosphate P-PO4 3- (g/kg) of organic manure from cattle and swine farms during composting. The results revealed a pH variation between 6.9 and 8.23 during composting, which is normal for compost, as mentioned in the literature. A high water content of over 90% was preserved in organic manure and compost because the samples were very liquid. Nutrient values showed increased ammonium and total inorganic nitrogen in cattle farms and one pig farm during composting. This study highlights a rise in nutrient values, especially of ammonium and total inorganic nitrogen in both cattle and pig farms, an aspect that reinforces the need to evaluate intervention strategies and develop a set of recommendations leading to the reduction of exposure risks and a subsequent reduction in human health impacts.